Identification of Commercial Fish Caught by Fishermen in the Lower Barumun River as Practicum Support Vertebrate Zoology Course - Malau, Nurul Hidayah; Khairul, Khairul; Siregar, Zunaidy Abdullah (Universitas Labuhanbatu, 2024)
Recognizing fish through morphological traits is an important aspect in developing taxonomic skills. It is evident that current students lack the ability to classify fish by species and group. Equipping students with this skill is essential as it serves as a valuable soft skill for future educators. The main objective of this study was to determine the commercial fish species in the downstream area of Barumun River. This study used an exploratory approach, which aims to obtain information on an unknown problem, using identification techniques involving observation of morphological traits and references from fish identification sources such as fish identification books and the Fishbase website. Fish taxonomy in this study relied on data sourced from the International Union for Conservation of Nature (IUCN) website. The results showed that there are 18 species of commercial fish living in the Barumun River, all of which belong to the category of true bony fish